Produção de butanol a partir de etanol utilizando óxidos mistos de Mg e Al - Simões, Jana Marimon (2016)
Butanol is an alcohol with a number of applications in various industries. It has diverse applications as solvent, and now shown to be an interesting substitute component for gasoline. His achievement is made from oil, but these days, many routes of synthesis from renewable raw materials have been studied, one of them the Guerbet reaction. The present concern about the environment shows the need to obtain such alcohol through a clean route. The use of catalysts is a great way to synthesize cleanly and to facilitate reproducibility. The hydrotalcites are inexpensive catalysts, easy synthesis and numerous applicability. This study aims to investigate and analyze the production of butanol from ethanol using mixed oxides of magnesium and aluminum obtained from hydrotalcites with 4 different molar ratios of magnesium and aluminum. For this, the syntheses were made of magnesium and aluminum hydrotalcites with molar ratios equal to 3, 5, 8 and 10 that were further calcined to obtain mixed oxides. The structures of the synthesized materials were analyzed to confirm the desired formation and to verify the properties there of. Preliminary tests were performed in triplicate between them to choose the most suitable catalyst for an attempt to optimize butanol to obtain varying power parameters like nitrogen flow and the fraction of ethanol. Two of the catalysts obtained poor results and two others obtained similar results in terms of selectivity and yield of butanol. To make the decision between the last two catalysts, stability tests were performed. With the stability test was chosen as the molar ratio of magnesium and aluminum catalyst equal to 5. With this catalyst were made over 8 reactions, according to the planning of the star type experiments. And as a result, for all reactions, it was found that increasing conversion of ethanol depends directly on the temperature increase. It was observed that butanol selectivity behavior directly depends on the ethanol fractions and the nitrogen flow in the reactor feed. Ethylene, ethanol dehydration product was the major main product at elevated temperatures, indicating that this reaction is more favored with increasing temperature than the reactions which lead to the production of butanol. Finally it proposed a reaction system that explains the conversion of ethanol in all observed products.